Reverse Visually Guided Reaching in Patients with Parkinson’s Disease - Pauline Gaprielian; Stephen H. Scott; Ron Levy (Parkinson's Disease)
In addition to motor symptoms such as difficulty in movement initiation and bradykinesia, patients with Parkinson’s disease (PD) display nonmotor executive cognitive dysfunction with deficits in inhibitory control. Preoperative psychological assessments are used to screen for impulsivity that may be worsened by deep brain stimulation (DBS) of the subthalamic nucleus (STN). However, it is unclear whether anti-Parkinson’s therapy, such as dopamine replacement therapy (DRT) or DBS, which has beneficial effects on motor function, adversely affects inhibitory control or its domains. The detrimental effects of STN-DBS are more apparent when tasks test the inhibition of habitual prepotent responses or involve complex cognitive loads. Our goal was to use a reverse visually guided reaching (RVGR) task, a hand-based version of the antisaccade task, to simultaneously measure motor performance and response inhibition in subjects with PD. We recruited 55 healthy control subjects, 26 PD subjects receiving treatment with DRTs, and 7 PD subjects receiving treatment with STN-DBS and DRTs. In the RVGR task, a cursor moved opposite to the subject’s hand movement. This was compared to visually guided reaching (VGR) where the cursor moved in the same direction as the subject’s hand movement. Reaction time, mean speed, and direction errors (in RVGR) were assessed. Reaction times were longer, and mean speeds were slower during RVGR compared to VGR in all three groups but worse in untreated subjects with PD. Treatment with DRTs, DBS, or DBS + DRT improved the reaction time and speed on the RVGR task to a greater extent than VGR. Additionally, DBS or DBS + DRT demonstrated an increase in direction errors, which was correlated with decreased reaction time. These results show that the RVGR task quantifies the benefit of STN-DBS on bradykinesia and the concomitant reduction of proactive inhibitory control. The RVGR task has the potential to be used to rapidly screen for preoperative deficits in inhibitory control and to titrate STN-DBS, to maximize the therapeutic benefits on movement, and minimize impaired inhibitory control.